1970
DOI: 10.3329/blj.v1i1.2623
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of anti-HEV and HEV RNA among volunteer blood donors and patients with Hepatitis B and C in Iran

Abstract: Aim: To assess seroprevalence of antibodies to hepatitis E virus (HEV) in healthy blood donors and hepatitis B, C patients. Methods: 450 subjects consisted of 200 blood donors in Tehran blood transfusion center, 100 subjects with hepatitis C and 150 subjects with hepatitis B infection enrolled in this study. The A549 cell line was grown in mixed medium. Cells were infected with hepatitis E virus that was purified from stool sample of a patient confirmed for hepatitis E infection by reverse transcription-polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“… Forest plot meta-analysis of seroprevalence of hepatitis E virus infection in Middle Eastern countries [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , ...…”
Section: Figurementioning
confidence: 99%
“… Forest plot meta-analysis of seroprevalence of hepatitis E virus infection in Middle Eastern countries [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , ...…”
Section: Figurementioning
confidence: 99%
“…Although the fecal-oral route is the main route of HEV transmission, the recent studies have demonstrated transfusion of HEV infection via blood products [4][5][6]. Previous seroprevalence studies among blood donors in Iran showed variable rates of anti-HEV antibodies of 4.5-16.7% [7][8][9][10][11]. As patients undergoing chronic hemodialysis have impaired immunity and a history of blood transfusion, they are at risk of nosocomially and parenterally transmition agents [12,13].…”
Section: Introduction *mentioning
confidence: 99%